Odpowiedzi

2010-03-09T14:40:35+01:00
D) { x+4y= 11/*(-2)
{ 2x+5y=10

{ -2x-8y= -22
{ 2x+5y=10
-----------------
-3y=-12
y=4

y=4
x=11-4*4=-5



e) { 4x+5y= -4/*3
{ 6x+7y= -6/*(-2)

12x+15y=-12
-12x-14y=12
--------------
y=0

y=0
4x+5*0=-4

y=0
4x=-4

y=0
x=-1

f) { 2x-11y= 73/*3
{ 3x-4y= 47/*(-2)

{ 6x-33y= 219
{ -6x+8y= -94
------------------------
-25y=125
y=-5


2x-11*(-5)=73
2x=73-55
2x=18
x=9

{y=-5
{x=9

g) { -2x+5y= -10/*7
{ 7x-4y= 8/*2

{ -14x+35y= -70
{ 14x-8y= 16
----------------------
27y=-54
y=-2

-2x+5*(-2)=-10
-2x=-10+10
x=0


y=-2
x=0